2015
DOI: 10.4314/jab.v90i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey on schistosomiasis caused by <i>Schistosoma haematobium</i> and <i>Schistosoma mansoni</i> in primary schools in the Sub-Division of Taïbong-Dziguilao, Far-North Region Cameroon

Abstract: Objective: To assess the current state of schistosomiasis (Schistosoma haematobium and Schistosoma mansoni) in Taïbong Sub Division, in Mayo-Kani Division, an epidemiological survey was conducted from September to November 2014 in four government primary schools, to determine the prevalence of these human parasites. Methodology and results: 360 pupils responded to a previously developed questionnaire and underwent urine and stool tests. The examination of urinary sediment and stool samples under the microscope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 3 publications
1
5
3
4
Order By: Relevance
“…The prevalence of S. haematobium infection recorded among school children contrasts other studies in Cameroon [30, 54] as well as other parts of Africa [55], which reported peak prevalence of UGS among school-aged children. In corroboration with the findings of Houmsou [21], in Nigeria, children of preschool age were found to have a higher prevalence of egg excretion (OR = 2.54) than those of the older age groups.…”
Section: Discussioncontrasting
confidence: 95%
“…The prevalence of S. haematobium infection recorded among school children contrasts other studies in Cameroon [30, 54] as well as other parts of Africa [55], which reported peak prevalence of UGS among school-aged children. In corroboration with the findings of Houmsou [21], in Nigeria, children of preschool age were found to have a higher prevalence of egg excretion (OR = 2.54) than those of the older age groups.…”
Section: Discussioncontrasting
confidence: 95%
“…Elle est donnée par la formule suivante : P= IP/N×100. Le test statistique du khi-deux (Schwartz, 1996) (Saotoing et al, 2011); 63,8% à Djohong dans la région de l'Adamaoua au Cameroun, 28,85% dans le Mayo-Louti, région du Nord Cameroun (Saotoing et al, 2014); 43,5% à Butajira en Ethiopie (Belyhun et al, 2011); 05,83% chez les élèves des écoles primaires de l'arrondissement de Taïbong-Dziguilao, Extrême-Nord Cameroun (Dankoni et al, 2015). Par rapport à la divergence des prévalences parasitaires observées, il y a lieu de tirer une conclusion selon laquelle les prévalences parasitaires varient d'un lieu à l'autre et en fonction de plusieurs facteurs parmi lesquels les conditions climatiques, socio-économiques, la surpopulation, la promiscuité, le manque de connaissances en matière d'hygiène individuelle, l'absence d'assainissement collectif.…”
Section: Analyse Statistiqueunclassified
“…Le taux d'infestation par Schistosoma haematobium (19,26%) est le plus élevé par rapport à celui de Schistosoma mansoni (2,22%). Des études antérieures menées dans les régions septentrionales du Cameroun ont révélé que la bilharziose vésicale est la plus répandue (Massenet et al, 2009 ;Saotoing et al, 2014 ;Dankoni et al, 2015 Figure 4.…”
Section: Prévalences Des Schistosomesunclassified
See 1 more Smart Citation
“…Trois formes sont classiquement observées: myélitique transverse aiguë ou subaiguë, compressive et radiculaire [ 8 - 11 ]. Ici, l´origine et la résidence de la fillette en zone d´endémie de la bilharziose urinaire en Afrique [ 12 ], et particulièrement en région septentrionale du Cameroun où S. haematobium est largement plus répandu [ 13 , 14 ] et les œufs de schistosomes avec éperons terminaux nous confortaient sur l´espèce en cause. Par ailleurs, les conditions écologiques y seraient plus propices pour le développement des hôtes intermédiaires de Schistosoma haematobium au détriment de S. mansoni .…”
Section: Discussionunclassified